The influence of production planning on business performance as a risk management technique in the manufacturing industry - Mogano, M. M. K. (Vaal University of Technology, 2021)
Production planning in the manufacturing industry has previously been viewed as a less strategic function for achieving businesses’ bottom-line goals. Many companies in the manufacturing industry focus more on strategic sourcing and cost saving initiatives for financial profits and often neglect the operational planning initiatives. The purpose of this study was to examine the influence of production planning on business performance as a risk management technique. A quantitative approach was adopted for the study and a questionnaire was distributed physically and electronically to production managers, operation managers, supply chain managers and general managers; 306 respondents participated. The data obtained were analysed by means of the Statistical Packages for the Social Sciences (SSPS). Model fit and hypotheses between the relationships identified in the study were tested through the Smart PLS 3 software. Business performance was evaluated through four indicators, namely production planning, production scheduling, lead time delivery and first to market. The results of the study show that production planning has a positive impact on the production scheduling function for lean production cost saving initiatives. The study also found that production planning positively influences lead time delivery and first to market because it manages the flow of material, production and delivery to the end user. Production scheduling and first to market proved to have very significant and positive relationships with business performance. These constructs have proved to deliver a competitive advantage and also improved customer satisfaction. The findings of this study present general key strategies to improve operational efficiencies and this study can contribute to increasing the literature in lean manufacturing and production excellence.
M. Tech. (Department of Logistics Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Influence of production planning; Business performance; Risk management technique; Manufacturing industry; Dissertations, Academic -- South Africa; Production planning; Manufacturing industries; Risk management